Upravljačko-informatički sustav u željezničkom prometu - Šimulčik, Damir (Promet - Traffic&Transportation, 2012)
The author discusses the process of rationalization by introduction of the ŽEPK management and information system in the Rail Transport Company of Zagreb and reviews its technical and technological and economic effects. Then the author provides the assessment of recommendations with reference to the fact that the very process as a segment cannot yield the wanted effects on the entire system unless synchronized on the entire network of Yugoslav Railways. This brings us to the fact that our only prospective refers to the synchronous activities and integration into the European rail system as a partner in its own right. The path leading to the materialization of this as compared to the current state of affairs appears to be a difficult one however any failure to integrate leads us into an unavoidable traffic isolation to inevitably exhibit adverse influence onto our entire social/ economic development in the future.